Macrophages in aseptic loosening: Characteristics, functions, and mechanisms - Cong, Yehao; Wang, Yi; Yuan, Tao; Zhang, Zheng; Ge, Jianxun; Meng, Qi; Li, Ziqing; Sun, Shui (Frontiers in Immunology, 2023)
Aseptic loosening (AL) is the most common complication of total joint arthroplasty (TJA). Both local inflammatory response and subsequent osteolysis around the prosthesis are the fundamental causes of disease pathology. As the earliest change of cell behavior, polarizations of macrophages play an essential role in the pathogenesis of AL, including regulating inflammatory responses and related pathological bone remodeling. The direction of macrophage polarization is closely dependent on the microenvironment of the periprosthetic tissue. When the classically activated macrophages (M1) are characterized by the augmented ability to produce proinflammatory cytokines, the primary functions of alternatively activated macrophages (M2) are related to inflammatory relief and tissue repair. Yet, both M1 macrophages and M2 macrophages are involved in the occurrence and development of AL, and a comprehensive understanding of polarized behaviors and inducing factors would help in identifying specific therapies. In recent years, studies have witnessed novel discoveries regarding the role of macrophages in AL pathology, the shifts between polarized phenotype during disease progression, as well as local mediators and signaling pathways responsible for regulations in macrophages and subsequent osteoclasts (OCs). In this review, we summarize recent progress on macrophage polarization and related mechanisms during the development of AL and discuss new findings and concepts in the context of existing work.